Does Innovative Development Drive Green Economic Growth in Resource-Based Cities? Evidence From China - Zhang, Ming; Yan, Taihua; Ren, Qingzhong (Frontiers in Environmental Science, 2022)
Seeking innovative development has become a necessity for global cities because of the accelerating consumption of natural resources and the increasing need for urgent control of environmental pollution. However, few studies have reported on the effect of innovative development on the green economic growth of resource-based cities. Therefore, this study aimed to construct the SBM model of unexpected output to measure the efficiency of green economic growth using data of 108 resource-based cities in China from 2004 to 2018, and to analyze the impact of innovative development and resource endowment on green economic growth using the systematic Generalized Method of Moments (GMM) model. The following results were obtained: first, the green economic growth efficiency of resource-based cities exhibited a general trend of fluctuation and rise, but the efficiency of different resource-based cities was different in time and space. Second, although innovative development promoted the green economic growth of resource-based cities, the impact of different resource-based cities was heterogeneous. Innovative development promoted the green economic growth of resource-based cities in eastern China, comprehensive cities, metal cities, growth cities, and renewable cities. However, it had an inhibitory effect on the green economic growth of northeast China, west China, and oil–gas and nonmetal resource–based cities, but no significant effect on the green economic growth of other resource-based cities. Third, the nonlinear effect of resource endowment on the green economic growth of resource-based cities was not significant, but resource endowment had a “curse” effect on green economic growth. Meanwhile, heterogeneity analysis showed two effects of resource endowment on the green economic growth in different resource-based cities: curse and blessing. Fourth, the impact of innovative development on the green economic growth of resource-based cities was moderated by resource endowment. The impact of innovative development on green economic growth decreased with the increase in resource endowment. Therefore, resource-based cities should not only constantly increase innovation and improve resource utilization efficiency but also actively promote coordination and cooperation of regional resource-based industries so as to achieve green and sustainable development.